Shoulder Strength Imbalances as Injury Risk in Handball - Edouard, P.; Degache, F.; Oullion, R.; Plessis, J.-Y.; Gleizes-Cervera, S.; Calmels, P. (International Journal of Sports Medicine, 2013)
This study was conducted to analyze whether internal (IR) and external (ER) rotator shoulder muscles weakness and/or imbalance collected through a preseason assessment could be predictors of subsequent shoulder injury during a season in handball players. In preseason, 16 female elite handball players (HPG) and 14 healthy female nonathletes (CG) underwent isokinetic IR and ER strength test with use of a Con-Trex® dynamometer in a seated position with 45° shoulder abduction in scapular plane, at 60, 120 and 240°/s in concentric and at 60°/s in eccentric, for both sides. An imbalanced muscular strength profile was determined using statistically selected cut-offs from CG values. For HPG, all newly incurred shoulder injuries were reported during the season. There were significant differences between HPG and CG only for dominant eccentric IR strength, ER/IR ratio at 240°/s and for IRecc/ERcon ratio. In HPG, IR and ER strength was higher, and ER/IR ratios lower for dominant than for nondominant side. The relative risk was 2.57 (95%CI: 1.60–3.54; P<0.05) if handball players had an imbalanced muscular strength profile. In youth female handball players IR and ER muscle strength increases on the dominant side without ER/IR imbalances; and higher injury risk was associated with imbalanced muscular strength profile.
Keywords: sports injury prevention; rotator cuff strength; isokinetic; overhead sports; strength imbalance